Methodology Of Organization And Presentation Of Educational Texts For Explaining Speech Connections - Hamrayeva Muhayyo Erkin qizi (Peerian Journals Publishing, 2024)
This study explores the methodology of organizing and presenting educational texts for explaining speech connections, with a focus on enhancing language education in Uzbekistan. Using a mixed-methods approach, the research analyzed existing textbooks, surveyed language educators, and conducted focus group discussions and classroom observations. The findings revealed that while traditional educational texts provide a strong theoretical foundation, they often lack practical, context-based examples and cultural relevance, limiting students' understanding of speech connections. Educators emphasized the need for multimedia resources, such as videos and audio recordings, to supplement textbook content, leading to a 15% improvement in student comprehension in multimedia-supported lessons. Additionally, the study highlighted the importance of incorporating Uzbek cultural elements into teaching materials to create a more engaging and relatable learning experience. A significant area for improvement identified was the progression of content complexity, with a need for more gradual transitions from simple to advanced concepts. The study concludes that a balanced approach combining traditional methods with modern interactive tools and culturally contextualized examples can significantly improve the effectiveness of language education in Uzbekistan, enhancing students' mastery of speech connections and their ability to communicate effectively in diverse contexts
Keywords: speech connections; language education; educational texts